Тhe main stakeholders and the policy of development of small and medium-sized businesses in the republic of kazakhstan - Karabalina, R.; Tuleugalieva, Zh. (Жәңгір хан атындағы БҚАТУ, 2023)
The global economy and various aspects of public life have been significantly impacted by the ongoing COVID-19 pandemic. One area that has been particularly affected is small businesses, which have faced significant challenges during this crisis and have required assistance from the government. The relevance of this article lies in the fact that the development of the small business sector is a priority in Kazakhstan's national policy, and it is crucial for the country's economy to stabilize the situation and recover from the crisis as soon as possible. Продолжающаяся пандемия COVID-19 оказала существенное влияние на мировую экономику и различные аспекты общественной жизни. Одной из областей, которая особенно пострадала, является малый бизнес, который столкнулся с серьезными проблемами во время этого кризиса и нуждался в помощи со стороны правительства. Актуальность данной статьи заключается в том, что развитие сектора малого бизнеса является приоритетом национальной политики Казахстана, и для экономики страны крайне важно стабилизировать ситуацию и как можно скорее выйти из кризиса.
«ҒЫЛЫМҒА ЖОЛ – 2023» білім алушыларға арналған халықаралық ғылыми-тәжірибелік конференциясының МАТЕРИАЛДАР ЖИНАҒЫ
СБОРНИК МАТЕРИАЛОВ Международной научно-практической конференции обучающихся «ПУТЬ В НАУКУ – 2023»
65 K21 Karabalina, R. Тhe main stakeholders and the policy of development of small and medium-sized businesses in the republic of kazakhstan / R. Karabalina, Zh. Tuleugalieva, науч. рук., Ж. Тулеугалиева. - Текст : непосредственный // Ғылымға жол-2023: білім алушыларға арналған халықаралық ғылыми-тәжірибелік конф. мат. жинағы (12 сәуір 2023 ж.). = Путь в науку-2023: сб. мат. междунар. науч.-практ. конф. обучающихся (12 апреля 2023 г.). = THE PATH TO SCIENCE – 2023: collected papers of the International Scientific-Practical Conference of students (12th of April, 2023). - Орал: Жәңгір хан атындағы БҚАТУ. - 2023. - Т. ІІ. - Б. 421-425 (Орал)
Keywords: отечественное издание; ЗКАТУ; конференции; экономика; малый бизнес; государственная поддержка; эпидемия; меры поддержки бизнеса; epidemic; business support measures